Adrenomedullin Signaling Pathway Polymorphisms and Adverse Pregnancy Outcomes - Lenhart, Patricia M.; Nguyen, Thutrang; Wise, Alison; Caron, Kathleen M.; Herring, Amy H.; Stuebe, Alison M. (American Journal of Perinatology, 2014)
Objective Reduced maternal plasma levels of the peptide vasodilator adrenomedullin have been associated with adverse pregnancy outcomes. We measured the extent to which genetic polymorphisms in the adrenomedullin signaling pathway are associated with birth weight, glycemic regulation, and preeclampsia risk.Study Design We genotyped 1,353 women in the Pregnancy, Infection, and Nutrition Postpartum Study for 37 ancestry-informative markers and for single-nucleotide polymorphisms in adrenomedullin (ADM), complement factor H variant (CFH), and calcitonin receptor-like receptor (CALCRL). We used linear and logistic regression to model the association between genotype and birth weight, glucose loading test (GLT) results, preeclampsia, and gestational diabetes (GDM). All models were adjusted for pregravid body mass index, maternal age, and probability of Yoruban ancestry. p values of < 0.05 were considered statistically significant.Results Among Caucasian women, ADM rs57153895, a proxy for rs11042725, was associated with reduced birth weight z-score. Among African-American women, ADM rs57153895 was associated with increased birth weight z-score. Two CALCRL variants were associated with GDM risk. CFH rs1061170 was associated with higher GLT results and increased preeclampsia risk.Conclusion Consistent with studies of plasma adrenomedullin and adverse pregnancy outcomes, we found associations between variants in the adrenomedullin signaling pathway and birth weight, glycemic regulation, and preeclampsia.
Keywords: adrenomedullin; genetics; gestational diabetes; preeclampsia; single nucleotide polymorphisms